To Increase the Degree of Capture of Fine-Grained Dust Particles, the Development of a Mathematical Model of the Motion and Separation of Solid Particles during Dynamic Regeneration - Akhmedova, Malika (International Journal of Psychosocial Rehabilitation, 2020)
Increasing the capture of fine dust particles, energy-saving mesh devices (dust collectors) are installed. Dust collectors are installed with dust retention with small dust collectors as a second step after existing equipment. Retention of fine dust particles that have not been completely cleaned will increase dust removal efficiency and reduce the environmental impact of dust. The use of such dust collectors for cleaning fine dust particles formed in the production department. The dust emission does not exceed the maximum permissible dust emissions (MPE).